(untitled) (The Pretoria Student Law Review, 2021)
In South Africa, asylum seekers and refugees are expected to integrate themselves into the society. In order to integrate themselves into society, refugees and asylum seekers seek employment. The employment of refugees and asylum seekers in South Africa is challenging. The right to work of refugees is guaranteed by section 27(f) of the Refugees Act, whilst section 22 provides for the right to work of asylum seekers. However, there is a noticeable gap between the provision of this right to work in terms of the Refugee Act and the actual recognition of this right by employers and professional councils. In practice, asylum seekers and refugees are frequently barred from exercising their right to work and thus do not enjoy these protected rights.9 This article, in analysing the difficulty of attaining employment, will firstly set a foundational basis in chapter 2. Chapter 3 will deal with the international framework governing the right to work of asylum seekers and refugees. Chapter 4 of this essay will then deal with the constitutional framework governing the right to work. In chapter 5, the implications of a limitation on the right to choose employment on the right to work will be dealt with. In chapter 6, the specific challenges faced by asylum seekers and refugees concerning their right to work will be discussed, along with recommendations for overcoming these challenges. Lastly, in chapter 7, there will be a summation of the main impediments and suggested palliatives for the realisation of the right to work of refugees and asylum seekers.